DARI VIDEO KE TOKO: BUDAYA KONSUMEN MELALUI MEDIA SOSIAL TIKTOK SHOP: Pola Konsumsi pada Mahasiswa Milenial Bangka Belitung - Rosmiati, Risti (Saskara : Indonesian Journal of Society Studies, 2022)
This study aims to analyze and find out from videos-based social media to virtual stores that create consumerism culture through social media TikTok Shop on Bangka Belitung millennial female students. This research is attractive because the development of features in the Tiktok application, namely Tiktok Shop, can construct consumptive behavior. This study used the descriptive qualitative method. The data collection technique was carried out by unstructured interviews with purposive sampling method. The results of this study (1) indicate that consumption patterns on TikTok Shop social media are in the form of intensity in watching live streaming and short video product reviews from buyers, (2) assume that online shopping is effective and efficient, and (3) become more trusting in the authenticity of goods because promotional media will see goods directly. This consumption pattern creates a consumer culture through the TikTok Shop social media. There are 3 driving factors for the millennial generation to create consumer culture, which are: (1) Lifestyle, (2) Mass Industry, (3) Symbolic significancy of goods. This study hoped that the public will not be trapped in false awareness and not be easily persuaded by advertisements. Capitalists have succeeded in playing a role in confusing between wants and needs and creating consumptive behavior.